(untitled) (International Journal of Nursing Education, 2020)
Stress is non-ended problem associated with learning. Coping styles are the only approaches that helpstudents to overcome the stress and enhance the educational success. The study aimed to identify stress areas and coping styles of nursing students. A descriptive research design was used. 118 nursing students wereasked to fill out the questionnaire. The highly learning environment stressors were coming from assignmentsand workload (12.14+4.19) and taking care of patients (10.14+4.19). The highly used coping styles werereligion (3.28 + 1.0), Acceptance (3.06 + 0.89) and active coping (2.92 + 0.68).. It can be concluded that theclinical workload found in the courses is the common stressor for last year students.